How Does Customer Service Offshoring Impact Customer Satisfaction?. Issue 6 (1st November 2020) - Whitaker, Jonathan; Krishnan, M.S.; Fornell, Claes; Morgeson, Forrest
ABSTRACT: Information technology (IT) plays a vital role in customer relationship management (CRM), because CRM processes include the collection and analysis of customer information, firms use technology tools to interact with customers, and IT created the conditions under which firms can offshore CRM processes. Customers have negative perceptions toward offshoring, which suggests that firms might be reluctant to offshore IT-enabled CRM processes. However, firms have significantly increased offshoring for CRM processes, presenting a conundrum. Why would firms increase offshoring for CRM processes if there could be a risk to customer satisfaction? This paper helps to resolve the conundrum by studying the impact of CRM sourcing on customer satisfaction with the firm's products and services, as measured by the American Customer Satisfaction Index TM . We analyze data for 150 North American firms and business units over a nine-year period. Front office offshore outsourcing and front office onshore outsourcing are both negatively associated with customer satisfaction, which suggests that negative customer perceptions may be due to the firm boundary dimension rather than the geographic location dimension. Front office offshore outsourcing is not statistically significant for services firms, which suggests that customers are more accepting of offshore providers in a service setting. Over time, the coefficient for back office offshore outsourcing has become more positive, which suggests that firms may expect to see a similar improvement for front office offshore outsourcing in the future. Our empirical results provide a basis to understand why firms have increased IT-enabled CRM offshoring despite short-term risks to customer satisfaction.